The Realization of the Bad Impact of Early Capitalism in Oscar WildeÃ¢â‚¬â„¢s Ã¢â‚¬Å“The Happy PrinceÃ¢â‚¬Â - Holis, Nor; Asmarani, Ratna (Universitas Negeri Semarang, 2019)
Living under feudalism and capitalism seems very good for those who were born from rich people. It is because they do not have to struggle of their life and would get everything as desire. Meanwhile, it is very hard for poor people because their live is worse and if they do not struggle of the life they might die. Ã¢â‚¬Å“The Happy PrinceÃ¢â‚¬Â is the story that shows how the feudalism and early capitalism work in the society. People live contradictory under those systems. Fortunately, since the capitalism applies, the poor people find new hope. Their laborpower is paid so that they are to feed themselves and the family. Besides, they work for the capitalistsÃ¢â‚¬â„¢ happiness. This new term of live is not a big different from feudal system. The payment for the poor who work is a very little difference that makes the poor happy. This research aims to describe how the feudalism and the early capitalism work in the short story. Using the sociological approach as to the evidences of the feudalism and the early capitalism system in the story is chosen to describe the impacts of those systems toward society. The result of this research shows that poor people accept the system of capitalism than the feudalism. It is because their labor-power is paid. This condition is different from previous system (feudalism) that makes poor people are getting worse because they must work freely.